Evaluación de la gestión administrativa del subproceso de rehabilitación, bienestar e inclusión social del GAD municipal Cantón Bolívar periodo 2015-20l6. - Mora Alcívar, María Fernanda (2018)
The purpose of the evaluation of the administrative management of the Rehabilitation, Welfare and Social Inclusion Subprocess of the Municipal Autonomous Decentralized Government of the Bolívar canton, was to know the administration in the resources consigned by the Cantonal Government. In the first place, the organizational structure and the administrative management system were identified, then, through the interview, information was collected on the personnel involved, number of beneficiaries, laws that are governed by the area, among others. Likewise, the design and application of the checklist was necessary to know the direction taken by the assigned resources, as well as to carry out the analysis of the administrative process developed in the institution in its stages (planning, direction, evaluation and control) and through the Balanced Scorecard tool management was required. Finally, an improvement plan was carried out to promote efficiency and effectiveness in the subprocess, applying a model of administrative management, which avoids duplicating efforts and guaranteeing the true service of quality and warmth.